Investigação do Impacto de Técnicas de Acionamento de Motores sobre a Qualidade de Tensão da Rede Elétrica - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The starting of induction motors has a relevant impact on the quality of the voltage in the electrical network. Conventionally, direct or electromechanical starting methods can introduce high starting currents and thus result in voltage dips in the electrical supply circuit. On the other hand, electrical networks with great distances and that supply poorly sized loads tend to accentuate voltage quality problems. This work presents a comparative study between three-phase induction motor drive techniques and the impact on the quality of the electrical network voltage. The following starting techniques were implemented: direct, autotransformer, soft-starter and frequency inverter. The mechanical torque profile as a function of engine speed is quadratic and was chosen to contemplate irrigation pumps for rice crops. The starting methods, as well as the induction motor models were organized in Matlab Simulink environment. In addition, a radial power system was considered, which represents a medium voltage feeder and a transformer, where the motor to be driven is located in the low voltage circuit. It was found that the frequency inverter, even without the use of any type of filter and with the simplest rectifier, manages to command the motor to start, causing a maximum voltage drop that is slightly greater than that of the motor in steady state. It was also possible to observe that soft-starters manage to smooth the machine’s torque, but are less effective than autotransformers when it comes to reducing the voltage drop during starting. Keywords: Starting Induction Motors. Power Electronics. Power Quality.
Keywords: Engenharia elétrica; Motores elétricos de indução; Eletrônica de potência; Electrical engineering; Electric motors, Induction; Power electronics; CNPQ::ENGENHARIAS